Design and development of a secure certificateless proxy signature based (SE-CLPS) encryption scheme for cloud storage - K. Sudharani, Ms.; N. K. Sakthivel, Dr. (International Journal of Engineering and Technology, 2021)
Certificateless Public Key Cryptography (CL-PKC) scheme is a new standard that combines Identity (ID)-based cryptography and tradi- tional PKC. It yields better security than the ID-based cryptography scheme without requiring digital certificates. In the CL-PKC scheme, as the Key Generation Center (KGC) generates a public key using a partial secret key, the need for authenticating the public key by a trusted third party is avoided. Due to the lack of authentication, the public key associated with the private key of a user may be replaced by anyone. Therefore, the ciphertext cannot be decrypted accurately. To mitigate this issue, an Enhanced Certificateless Proxy Signature (E-CLPS) is proposed to offer high security guarantee and requires minimum computational cost. In this work, the Hackman tool is used for detecting the dictionary attacks in the cloud. From the experimental analysis, it is observed that the proposed E-CLPS scheme yields better Attack Detection Rate, True Positive Rate, True Negative Rate and Minimum False Positives and False Negatives than the existing schemes.Â Â Â